2017
DOI: 10.1002/jbm.a.36242
|View full text |Cite
|
Sign up to set email alerts
|

Pressure responsive nanogel base on Alginate‐Cyclodextrin with enhanced apoptosis mechanism for colon cancer delivery

Abstract: 5-Fluorouracil (5-Fu) commonly use in the treatment of different kinds of cancer, but limited cellular uptake and death is still a problem. Herein, we report a simple process for the synthesis of pressure-sensitive nanogels that indicate to be appropriate in the delivery of 5-Fu. The hydrogels (Al-CD) prepare by crosslinking of alginate (Al) with modified beta Cyclodextrin (β-CD) as Crosslinker. Next, nanoparticles obtaine by an emulsification method. 5-Fu as model drug loades into the Al-CD nanogels easily by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…βCyD in the alginate hydrogels plays a dual role of crosslinker and binding site for 5-flourouracil that results in controlled release of the drug with promising encapsulation efficiency in the alginate hydrogels. [60]…”
Section: Alginates: Cyd-modified Alginate Polymersmentioning
confidence: 99%
“…βCyD in the alginate hydrogels plays a dual role of crosslinker and binding site for 5-flourouracil that results in controlled release of the drug with promising encapsulation efficiency in the alginate hydrogels. [60]…”
Section: Alginates: Cyd-modified Alginate Polymersmentioning
confidence: 99%
“…The in vitro results exhibited that 5‐FU nanoparticles had an acceptable potential for treating colon cancer and could kill approximately 80% of the cancer cell line, HT‐29. Hosseinifar et al reported a newly published article on the preparation of pressure sensitive 5‐FU‐loaded nanogels based on alginate modified with β‐cyclodextrin as cross‐linker through emulsification method. Their obtained results showed that the nanogels containing the drug could be employed as an excellent candidate to overcome the inefficiency of the drug using exclusively in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the cisplatin-loaded alginate nanogels showed highly pH-responsive drug release behavior and were capable of selective NIR fluorescence imaging and chemotherapy of macrophage cells. Another method for the preparation of pressure-sensitive 5-fluorouracil-loaded nanogels was described by Hosseinifar et al[ 31 ]. Hydrogels were obtained via crosslinking of alginate with modified beta-cyclodextrin as a crosslinker, and then nanosized gels were produced by an emulsification method.…”
Section: Methods For Constructing Alginate-based Drug Delivery Plamentioning
confidence: 99%
“…The developed nanogels had an average particle size of 55.1 ± 5.1 nm with a noticeable drug encapsulation (82.1 ± 5.7%), which could induce a higher 5-Fu intracellular accumulation and a significant cell death extension by an apoptotic mechanism. It is believed that alginate-based nanogels can protect encapsulated drugs from degradation and provide a controlled release profile [ 31 ].…”
Section: Methods For Constructing Alginate-based Drug Delivery Plamentioning
confidence: 99%